Endoscopic injection of adrenaline versus normal saline in bleeding peptic ulcer A prospective evaluation - Asreah, Rabah H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Endoscopic treatment is widely accepted as the most effective method for controlling acute ulcer bleeding and preventing ulcer rebleeding. Objective: is to compare efficacy and safety of local endoscopic injection of adrenaline to normal saline in bleeding peptic ulcers and to identify the risk of rebleeding after successful endoscopic hemostasis. Patients and methods: This is a prospective study of 77 patients with bleeding peptic ulcers were treated by local endoscopic injection of adrenaline or NS. Patients who succeeded initial hemostasis were admitted and followed for rebleeding events. Rebleeding was confirmed by urgent endoscopy followed by referral to urgent surgery. Outcome was measured directly by rebleeding rate, need for surgery, and the mortality rate and indirectly by the number of blood transfusion units and days of hospitalization. All clinical and endoscopic data of patients were collected to stratify the risk of rebleeding. Results: The rebleeding rates (17.9% for NS group vs. 11.4% for adrenaline group), the need for emergency operation (10.2% vs. 5.7%), blood transfusion (3.2 units vs. 2.4 units), hospital stay (2.8 days vs. 2.7 days) and in-hospital mortality (5.6% vs. 5.7%) were not significantly different in both groups. Clinical and endoscopic analysis revealed that presence of shock, coexisting disease, large ulcer size (>2cm) and active bleeding were independent factors predicting rebleeding. Conclusion: local endoscopic injection of NS and adrenaline are equally safe and effective in stopping ulcer bleeding and rebleeding. Severe bleeding, comorbidities, large ulcer size, active bleeding all are predictors of rebleeding.